2014
DOI: 10.1007/s00402-014-1983-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparing approaches to expose type C fractures of the distal humerus for ORIF in elderly patients: six years clinical experience with both the triceps-sparing approach and olecranon osteotomy

Abstract: Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
2
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 22 publications
3
44
2
7
Order By: Relevance
“…Zhang et al . compared triceps sparing with olecranon osteotomy approach in 67 patients with type C distal humerus fracture in an elderly population and concluded that triceps-sparing group has better functional outcomes, faster patient recovery, and lower complication rate, all without compromising visibility of articular surface or impairing fracture reduction during fixation 23. In our study, the mean MEPI score was 94.40 point, with 17 excellent, five good, three fair, and no poor grade, which is consistent with other published series 3102225.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al . compared triceps sparing with olecranon osteotomy approach in 67 patients with type C distal humerus fracture in an elderly population and concluded that triceps-sparing group has better functional outcomes, faster patient recovery, and lower complication rate, all without compromising visibility of articular surface or impairing fracture reduction during fixation 23. In our study, the mean MEPI score was 94.40 point, with 17 excellent, five good, three fair, and no poor grade, which is consistent with other published series 3102225.…”
Section: Discussionmentioning
confidence: 99%
“…Reconstruction of osteotomy may cause delayed union, non-union, and bump of implant, which may compel further surgery. Correspondingly, triceps-splitting method does not produce adequate exposure of the articular surface compared with other methods; this method has one further drawback of direct muscle trauma, causing fibrosis and disruption to inter-muscular nerve branches, which can lead to muscle weakness [12]. Alonso-Llames first reported the paratricipital method in 1972 for pediatric supra-condylar fractures treatment [13].…”
Section: Discussionmentioning
confidence: 99%
“…This enabled us to reassure patients to execute a full range of elbow motions without any worries regarding non-union of the osteotomy or loosening of the implantation. Alleviation of these worries allow patients to execute triceps exercises shortly subsequent to the operation and consequently did not endure much triceps strength loss [12]. Additionally, active and passive ROM exercises may have supported the prevention of triceps weakness and elbow stiffness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, surgeons can determine the trajectory of the locking screws in a distal humerus fracture treatment 11,12 , offering the surgeon a means to maximize xation in the distal fragments and providing the best possible outcome for the patient. However, the biomechanical properties of this plate xation system remain unknown.…”
Section: Cadaveric Bonementioning
confidence: 99%